Mitigation of salt stress in rice (oryza sativa l.) growth and yield in coastal saline soil using crop residue-driven organic amendments under varying moisture conditions - Sikder, Md Raisuddin; Khan, Md Harunor Rashid (Dhaka University Journal of Biological Sciences, 2024)
The increasing salinity in coastal areas due to climate change significantly hinders rice (Oryza sativa L.) production, a crucial food source for over half of the global population. This study evaluates the effects of organic amendments and moisture conditions on the vegetative growth and yield of rice varieties in a saline field in the Khulna district of Bangladesh. The field experiment was conducted from February to May 2020, using rice straw compost (RSC), sawdust (SD), rice husk (RH), and mustard seed meal (MSM) at varying rates (0, 5, 10, 15 t ha-1) under moist (70% soil moisture) and saturated (>100% soil moisture) conditions. The experiment featured BRRI dhan 28 (salt-sensitive) and BRRI dhan 47 (salt-tolerant) varieties. Key metrics evaluated in the study included the productive to unproductive tillers ratio (PTR), spikelet sterility, percent filled grains, straw yield, and grain yield. Results indicated significant (p ≤0.05) improvements in PTR, reduction in spikelet sterility, increased grain filling, and higher straw and grain yields with applying organic amendments, especially MSM. The highest PTR for BRRI dhan 47 (0.86) was achieved with MSM at 5 t ha-1 under moist conditions, while BRRI dhan 28 reached a PTR of 0.81 with RH at 10 t ha-1 under saturated conditions. Spikelet sterility was minimized (9/panicle) with MSM at 5 t ha-1 under saturated conditions for both varieties. Percent filled grains peaked (88.9%) with MSM at 5 t ha-1 for BRRI dhan 28. Enhanced straw yields were observed, with BRRI dhan 47 achieving 8.76 t ha-1 with MSM at 10 t ha-1. Grain yield increased significantly, with BRRI dhan 28 yielding 5.75 t ha-1 under similar conditions. The study confirms that organic amendments of MSM > RSC > SD > RH can effectively mitigate salt and moisture stress, thereby improving rice productivity in saline soils. Dhaka Univ. J. Biol. Sci. 33(2): 1-13, 2024 (July)